Comparative evaluation of simulators for practising fluoroscopy-guided renal pelvic puncture - N. K. Gadzhiev; D. S. Gorelov; A. A. Mishchenko; V. P. Britov; R. R. Kharchilava; E. F. Sharafutdinov; S. B. Petrov; D. D. Shkarupa (Вестник урологии, 2023)
Introduction. The skill of puncture of the kidney pelvicalyceal system is one of the basic urological skills, as it is used for various surgical interventions. There are different training models, from laboratory animals to virtual reality simulators.Objective. To evaluate a non-biological model of the pelvicalyceal system puncture simulator UroATOM (“Alfa-Rhythm”, Russian Federation) and to compare it with a virtual reality simulator PERC MentorTM (“Simbionix”, Beit Golan, Israel).Materials & methods. The results of fluoroscopic guided puncture training were analyzed among 50 physicians. The specialists were divided into two equal groups by experience: group 1 — beginners, group 2 — experienced urologists. In phase 1, both simulators were evaluated by the physicians using Likert questionnaires. In phase 2, the puncture results in beginners were evaluated before and after the UroATOM simulator practise.Results. Comparing the indices of both simulators showed that UroATOM was rated as more convenient to use (p = 0.0001) and cheaper (p < 0.0001). The analysis of the puncture performance by "beginners" before and after UroATOM training revealed a statistically significant improvement in the performance. The puncture time index improved by 79 seconds. The index of fluoroscopy duration decreased by 40.9 seconds. The number of puncture attempts decreased by 1.4 times. The amount of contrast decreased by 5.4 ml.Conclusions. The UroATOM simulator is effective for training young specialists in fluoroscopy-guided renal cavity puncture.